Antifungal effect of Malaysian aloe vera leaf extract selected fungal species of pathologenic otomycosis in in-vitro culture medium - Saniasiaya, Jeyasakthy (2017)
Introduction: Aloe barbadensis miller or Aloe vera has been used for therapeutic purposes since ancient time. Antifungal activity is amongst the medicinal properties owned by Aloe vera. This study proposes antifungal effect of Malaysian Aloe vera leaf extract on pathogenic otomycosis species, Aspergillus niger and Candida albicans. Methodology: This pilot study is a laboratory-controlled prospective study conducted in Universiti Sains Malaysia. Powdered form of Malaysian Aloe vera leaf was extracted with 70% ethanol and aqueous via Soxhlet extraction method, after being evaporated using rotary evaporator to a thicker compound. The concentrated extract is then freeze dried to obtain powdered form which is diluted into establish five different concentrations of 50 g/ml, 25 g/ml, 12.5 g/ml, 6.25 g/ml and 3.125 g/ml. Five replicates were performed for five different concentration. Results were statistically analysed using one-way ANOVA and independant-t test. Sabaroud Dextrose Agar lawned with tested fungal isolates were inoculated with the extracts using well-diffusion method. Zone of inhibition was measured followed by minimum inhibitory concentration. Results: For Aspergillus niger, zone of inhibition for alcohol and aqueous extract were obtained for all concentrations except 3.125g/ml. As for Candida albicans, there were no zone of inhibition for both alcohol and aqueous extract of Aloe vera leaf. The minimum inhibitory concentration value of aqueous and alcohol extracts were 5.129g/ml and 4.35g/ml for Aspergillus niger and as for Candida albicans, it was not determined as no zone of inhibition was obtained.